TECHNIKI OBRAZOWANIAThe diagnosis of pneumothorax – complication after cardiosurgery procedures - Głowacki, Jan; Pakosiewicz, Waldemar; Kucewicz, Ewa; Miszalski-Jamka, Karol; Karolak, Wojciech; Przybylski, Roman; Kluczewska, Ewa (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
Pneumothorax is one of the possible complications after chest procedures in cardiosurgery. Chest X-ray remains the first-line diagnostic modality in case of suspected pneumothorax. Its quality in the setting of the post-operation room is lower due to patient status and the possibility of acquiring only anterior-posterior projection. Meticulous analysis of the chest X-ray and clinical data allow for correct diagnosis without the need for computed tomography.